Field evaluation of power tiller rotavator with seating attachment - TIWARI, P S; VARSHNEY, A C; MEHTA, C R (The Indian Journal of Agricultural Sciences, 2013)
A 7.S kW rotary-type power tiller fitted with seating attachment was field evaluated for rotapuddling and rotatilling operations under soil conditions of Bhopal region and its performance was compared with that of power tiller without seating attachment. For rotapuddling operation, effective field capacity and fuel consumption of power tiller with seating attachment were 0.098 ha/hr and 1.350 litres/hr respectively compared with the respective values tor powertiIler without seating attachment 0.099 ha/hr and 1.300 litres/hr. For dry rotatilling the etTective field capacities ofpower tiller with and without seating attachment were 0.097 and 0.099 ha/hr. when operated in the plots of more than0.3 ha size. However, on per-day basis the toal area covered by power tiller with seating attachment was more, becausethe operator required less frequent rests of shorter duration (2 rest periods aggregating to 0.78 hr in a working day of6.65 hr) compared with that without seating attachment (4 rest periods aggregating to 1.95 hr in a working day of 7.33hr). Depth of operation was more uniform when power tiller was fitted with seating attachment, as the rotavator wasrestrained from coming out from the soil even at hard soil spots. Fuel consumption of power tiller with seating attachment during dry rotatilling was slightly more (1.280 litres/hr) than that of power tiller without seating attachmentÂ Â  (1.200 litres/hr).